Rare Case: 65 Year Old Man with Anteromedial Mediastinal Tumor (Thymic Carcinoma) Mimicking Lung Cancer - Lyono, Albert; Agus Setyawan, Ungky; Dwi Pratiwi, Suryanti; Rachma Erawati, Dini; Setyo Yudhanto, Hendy; Isharanto, Artono (Universitaas Brawijaya, 2026)
Background: Thymic carcinoma are very rare and often accompanied by metastases to other organs, pericardial effusion and pleural effusion where the 5-year survival rate is about 55%. Thymic carcinoma has several subtypes, squamous cell carcinoma and undifferentiated carcinoma. Case Report: A 65-year-old man coincidentally showed a mediastinal tumor on CXR while infected with COVID-19. Spirometry shows mild obstruction and restriction. Thorax CT scan suggests an anterior-middle mediastinal mass with left pleural effusion. The patient underwent a core biopsy followed by VATS tumor excision. Immunohistochemistry CK(+) and Vimentin(-) suggest a solid type adenocarcinoma, then Napsin A(-), TTF1(-), P40(+) suggest squamous cell carcinoma. The patient was diagnosed with left anteromedial mediastinal tumor (Thymic carcinoma: Squamous cell carcinoma) Masaoka stage III, left pleural effusion. The patient was treated with first line chemotherapy Carboplatin-Etoposide 6 series resulting stable disease followed by maintenance chemotherapy etoposide 6 series. The last RECIST suggests a solid malignant mass in the left lung (stable disease). Discussion: Surgery with radiotherapy is treatment for resectable cases but for unresectable cases chemotherapy with or without radiotherapy is preferred. The patient was unresectable case treated with chemotherapy. Thymic carcinoma has a poor response to chemotherapy with overall response rate around 22-36% but this patient has stable disease with chemotherapy. Conclusion: 65 years-old man without respiratory complaints diagnosed with unresectable thymic carcinoma and left pleural effusion, underwent chemotherapy with result stable disease up to 9 months continued maintenance therapy and become a resectable tumor. Keywords: Thymic carcinoma, Squamous Cell Carcinoma